Real-time detection of cerebrospinal fluid with bioimpedance needle in paediatric lumbar puncture - Sievänen Harri; Kari Juho; Halonen Sanna; Elomaa Timo; Tammela Outi; Soukka Hanna; Eskola Vesa (WILEY, 2025)
Background Lumbar puncture is a common clinical procedure that can occasionally be difficult. Various needle guidance methods can facilitate performing this procedure, but at the expense of special expertise, equipment and facility. In the present study, we evaluated the clinical feasibility of a novel bioimpedance needle system regarding its ability to detect cerebrospinal fluid (CSF) in paediatric lumbar punctures.
Methods We performed 40 lumbar puncture procedures using the bioimpedance needle system in 37 paediatric patients, aged from 0 days to 17 months, as a part of their prescribed examinations in two university hospitals. The bioimpedance needle is similar to a conventional 22G cutting-edge spinal needle with a stylet, except the needle and stylet are configured as a bipolar electrode with high spatial resolution. The system measures in real-time when the needle tip reaches the subarachnoid space containing CSF. The procedure was considered successful when the erythrocyte count was determined from the obtained CSF sample.
Results Subarachnoid space was verifiably reached in 28 out of 40 procedures (70%). Bioimpedance needle system detected CSF in 23 out of these 28 successful procedures (82%) while failed in 3 out of 28 procedures (11%). No adverse events were reported.
Conclusion Bioimpedance spinal needle system was found clinically feasible in paediatric lumbar punctures, and it may offer an objective and simple means to detect the time point when the needle tip is in contact with the cerebrospinal fluid.